2016
DOI: 10.1097/sle.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Laparoscopic Primary Repair in the Treatment of Colonic Perforation After Colonoscopy: A Review of 40,127 Patients

Abstract: Laparoscopic primary repair is safe and effective in resolving colonic perforation due to colonoscopy, and it might offer benefits over the open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Therefore, regions with acute angles and redundancy are the most frequent sites of colonoscopic perforation. As in our study, the most common perforation sites during colonoscopy are typically the sigmoid and rectosigmoid colon [17, 18, 20]. Of course, the redundant sigmoid colon would be the most suitable site for laparoscopic application of an endoscopic linear stapler.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, regions with acute angles and redundancy are the most frequent sites of colonoscopic perforation. As in our study, the most common perforation sites during colonoscopy are typically the sigmoid and rectosigmoid colon [17, 18, 20]. Of course, the redundant sigmoid colon would be the most suitable site for laparoscopic application of an endoscopic linear stapler.…”
Section: Discussionmentioning
confidence: 73%
“…Of these, 12 articles were excluded for the following reasons: no control group (n = 7); inadequate design (n = 2); no usable data (n = 2); mixed disease (n = 1). Ultimately, 11 articles [12,13,[18][19][20][21][22][23][24][25][26] (America = 2, Argentina = 1, Belgium = 1, Germany = 2, Korea = 3, China = 2) totaling 323 patients were finally eligible for the quality assessment,of whom 192 underwent LS and 131 underwent OS. A flowchart of the literature search and selection is illustrated in (Fig.…”
Section: Selected Studiesmentioning
confidence: 99%
“…Ten studies [12,13,[18][19][20][22][23][24][25][26] were included (LS = 182, OS = 128), and low heterogeneity among the studies (I 2 = 0%, P = .63). In the pooled data, there was no significant difference in sex ratio between the groups (OR = 1.35; 95% CI: 0.85 to 2.16; P = .20; Fig.…”
Section: Sex Ratiomentioning
confidence: 99%
“…The reasons may include the advantages of less trauma, less postoperative morbidity, less pain and shorter hospitalization 5. In recent years, some studies have reported that laparoscopic surgery is safe and effective in the treatment of colonic perforation 6. However, there has been no systemic report on the application of laparoscopy in SCP.…”
mentioning
confidence: 99%